2020
DOI: 10.1080/19490976.2020.1814121
|View full text |Cite
|
Sign up to set email alerts
|

A porcine ligated loop model reveals new insight into the host immune response againstCampylobacter jejuni

Abstract: The symptoms of infectious diarrheal disease are mediated by a combination of a pathogen's virulence factors and the host immune system. Campylobacter jejuni is the leading bacterial cause of diarrhea worldwide due to its near-ubiquitous zoonotic association with poultry. One of the outstanding questions is to what extent the bacteria are responsible for the diarrheal symptoms via intestinal cell necrosis versus immune cell initiated tissue damage. To determine the stepwise process of inflammation that leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…The degradation of the intestinal barrier can provide a beneficial environment for the proliferation of the pathogen and potentiate more severe disease symptoms. 51 The function of the intestinal barrier is related to many factors, including D-lactate, endotoxins in serum, and intestinal epithelial tight junction (TJ) proteins. 52,53 Elevated levels of D-lactate in serum are usually accompanied by impaired function of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of the intestinal barrier can provide a beneficial environment for the proliferation of the pathogen and potentiate more severe disease symptoms. 51 The function of the intestinal barrier is related to many factors, including D-lactate, endotoxins in serum, and intestinal epithelial tight junction (TJ) proteins. 52,53 Elevated levels of D-lactate in serum are usually accompanied by impaired function of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to infection with the C. jejuni wild-type strain, mice infected with the ciaD deletion mutant have reduced GI tract wall thickening and reduced inflammation of the ileocecocolic lymph node 23 . More recently, the application of a pig ligated loop model also revealed that a C. jejuni ∆ciaD mutant does not induce the characteristic robust inflammatory response observed with a C. jejuni wild-type strain, as demonstrated by the production of inflammatory cytokines and neutrophil markers 30 . Laboratory studies have shown that CiaD is mechanistically involved in host cell uptake of C. jejuni by promoting actin reorganization and membrane ruffling via Erk 1/2 activation 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain further insights into the responses of the potential core vaccine candidates and core VFs to different stresses, we selected two transcriptome data to analyze the gene expression in different experiments of human and pig ( Negretti et al, 2019 , 2020 ). In the environment of co-culturing with human INT 407 and Caco-2 cells, the expression levels of 126 genes, including the 25 core VFs (which include sodB , cadF , and flgC ) that were found in this study, were increased and the expression levels of 148 genes (including 13 core VFs) were decreased under human immune stress ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the flagellar genes are important VFs, which are essential for C. jejuni motility and the secretion of virulence proteins. The differences in the gene expressions could be caused by the different transcriptional responses by different hosts or the need for a certain reaction time after infection ( Negretti et al, 2020 ). In this study, transcriptome analysis of C. jejuni indicated that the core VFs play important roles under different stresses.…”
Section: Resultsmentioning
confidence: 99%